MENINGKATKAN KUALITAS PEMBELAJARAN MELALUI ACTIVE LEARNING IN HIGH EDUCATION (ALIHE) PADA MATA KULIAH PENDIDIKAN IPA SD DI JURUSAN PGSD FIP UNJ - A R Supriatna (Perspektif Ilmu Pendidikan, 2013)
The improvement of instructional quality, particularly in the Natural Science Course, in Primary School Teacher Education Departement of the School of Education, State University of Jakarta, has not well implemented active learning as required in ALIHE. The lecture plays more role directing the students rather than motivating the students to be active learning. The purpose of this research was to improve the instructional quality by implementing ALIHE in this Course. Employing action research method, the research was conducted at Primary School Teacher Education Departement of the School of Education, State University of Jakarta, as from February through June 2012. The data were collected using the observatuin sheets prepared in collaboration with Natural Science Lecturers responsible for the Course of Natural Science Education for Primary School. The findings concluded thet ALIHE strategy can (1) improve the instructional quality including the lecture’s performance and the learning effects for the students, (2) improve the appropriate instructional climate, (3) enable the the lecture or the lecture and the students design instructional materials and media which improve the learning achiievement, and (4) enable the lecture to determine more suitable instructional system.